2012
DOI: 10.1021/jf303881k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Odor-Active Compounds in Thai Durian (Durio zibethinus L. ‘Monthong’) by Aroma Extract Dilution Analysis and Headspace Gas Chromatography–Olfactometry

Abstract: An aroma extract dilution analysis applied on the volatile fraction isolated from Thai durian by solvent extraction and solvent-assisted flavor evaporation resulted in 44 odor-active compounds in the flavor dilution (FD) factor range of 1-16384, 41 of which could be identified and 24 that had not been reported in durian before. High FD factors were found for ethyl (2S)-2-methylbutanoate (fruity; FD 16384), ethyl cinnamate (honey; FD 4096), and 1-(ethylsulfanyl)ethanethiol (roasted onion; FD 1024), followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 36 publications
3
74
0
Order By: Relevance
“…A prominent role for these pathways in durian is supported in the literature, as VSCs have been identified as important components in durian odor 5,6,35 . Ethylene production and cellular respiration are also increased in durian fruits during the climacteric stage of ripening and are associated with important physiological changes, including odor production, pulp softening, sugar release, and water loss followed by dehiscence 1,36 .…”
Section: A R T I C L E Smentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent role for these pathways in durian is supported in the literature, as VSCs have been identified as important components in durian odor 5,6,35 . Ethylene production and cellular respiration are also increased in durian fruits during the climacteric stage of ripening and are associated with important physiological changes, including odor production, pulp softening, sugar release, and water loss followed by dehiscence 1,36 .…”
Section: A R T I C L E Smentioning
confidence: 99%
“…4a). Studies in microbes and plants have shown that MGL is a major functional contributor to VSC biosynthesis, degrading the sulfurcontaining amino acids cysteine and methionine into methanethiol, which is further broken down into di-and trisulfides 1,38,39 (Fig. 4b).…”
Section: Genomic Expansions Of Volatile Sulfur Compound Genesmentioning
confidence: 99%
“…In particular, hydrogen sulphide occurs in a wide variety of foods [1] and exhibits a characteristic smell usually referred to as rotten egg-like [1][2][3][4][5][6][7] and an odour detection threshold of 10 µg/L [8]. In food, hydrogen sulphide may be formed either enzymatically or thermally from cysteine or cysteine-containing peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Methanethiol is also a very common food volatile [1,21] and described as having a rotten and cabbage-like smell [5,6,22,23]. With 0.59 µg/L its odour detection threshold in water is even lower than that of hydrogen sulphide [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation